Marine Debris Mitigation Strategy in Supporting the Development of Sustainable Tourism in SEZ Mandalika Lombok - Astrini Widiyanti; Lalu Auliya Akraboe Littaqwa; Edwin Jefri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Concerns about increasing marine debris at priority tourist destinations in SEZ Mandalika require a comprehensive mitigation strategy. The purpose of this study is to analyze the characteristics of marine debris on three different types of beaches and to analyze marine debris mitigation strategies. Data collection was conducted by field survey with a transect methode. Marine debris mitigation strategies are identified quantitative SWOT analysis. Characteristics of macro marine debris at Tanjung Aan Beach based on the amount dominated 41% plastic. Meso marine debris is dominated by plastic foam in the form of white cork 48%. In the fishing area, the characteristics of marine debris is dominated type of cloth material 52% in the form of fishing thread and other fabrics. Meso marine debris in the fishing area dominated 45% in the form of white cork flakes. Characteristics of macro marine debris at Batu Berang Beach, it was found that fabric waste dominated 42%. Meso waste in Batu Beach is dominated 60% plastic. The alternative strategy that the highest score (2.99) is the sorting of organic and non-organic waste in various coastal typologies by visitors with the preparation of facilities and infrastructure by the tourism management or village government.